Expanding Diversity in Molecular Structures and Functions of the IL-6/IL-12 Heterodimeric Cytokine Family - Hasegawa, Hideaki; Mizoguchi, Izuru; Chiba, Yukino; Ohashi, Mio; Xu, Mingli; Yoshimoto, Takayuki (Frontiers in Immunology, 2016)
The interleukin (IL)-6/IL-12 family cytokines have pleiotropic functions and play critical roles in multiple immune responses. This cytokine family has very unique characteristics in that they are composed of two distinct subunits forming a heterodimer and each cytokine and receptor subunit shares with each other. The members of this cytokine family are increasing; currently, there are more than 6 cytokines, including the tentatively named cytokines IL-Y (p28/p40), IL-12 (p35/p40), IL-23 (p19/p40), IL-27 [p28/Epstein-Barr virus-induced protein 3 (EBI3)], IL-35 (p35/EBI3), and IL-39 (p19/EBI3). This family of cytokines covers a very broad range of immune responses, including pro-inflammatory responses such as helper T (Th)1, Th2, and Th17 to anti-inflammatory responses such as regulatory T (Treg) cells and IL-10-producing Treg cells. IL-12 is the first member of this family, and IL-12, IL-23, and IL-27 are mainly produced by activated antigen-presenting cells such as dendritic cells and macrophages. IL-12 plays a critical role in the promotion of Th1 immune responses by inducing interferon-γ production to combat pathogens and malignant tumors. IL-23 induces IL-17 production and is necessary to maintain pathogenic Th17 cells that cause inflammatory and autoimmune diseases. IL-27 was initially reported to play a critical role in promotion of Th1 differentiation; however, subsequent studies revealed that IL-27 has broader stimulatory and inhibitory roles by inducing IL-10-producing Treg cells. IL-35 is produced by forkhead box P3+ Treg cells and activated B cells and has immunosuppressive functions to maintain immune tolerance. The most recently identified cytokine, IL-39, is produced by activated B cells and has pro-inflammatory functions. The cytokine tentatively named IL-Y seems to have anti-inflammatory functions by inhibiting Th1 and Th17 differentiation. In addition, individual cytokine subunits were also shown to have self-standing activities. Thus, promiscuity within the IL-6/IL-12 family cytokines complicates structural and functional clarification and assignment of individual cytokines. A better understanding of the recent advances and expanding diversity in molecular structures and functions of the IL-6/IL-12 family cytokines could allow the creation of novel therapeutic strategies by using them as tools and targeted molecules.